Tingkat Pendidikan, Literasi Akuntansi, Dan Persepsi Pemilik Umkm Tentang Akuntansi Sebagai Determinan Penggunaan Informasi Akuntansi - Atika Jauharia Hatta; Oktyas Budiyati (AKUNTANSI DEWANTARA, 2021)
The main objective of this research is to determine the effect of MSME owners perception about using the accounting information, education level, and accounting literacy on the use of accounting nformation on MSME. Sample used in this study amounted to 93 respondents of MSME owner in Malioboro, Yogyakarta. Using multiple linier regression analysis the results shows that: (1) there is a positive the effect of MSME owner’s perception about the use of accounting information for MSME (2) level of education has no effect on the use of accounting information for MSME; (3) accounting literacy has a positive effect of accounting information for MSME.